The Teaching Barbies of Physical Education in Public High Schools - Vestil, Marijoy I.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
Education is a process of welcoming truth and opportunity. It is the prudent, encouraged, and respectful learning undertaken in the belief that all should have the chance to share in life. Befittingly, there are no gender biases when it comes to being a teacher. However, this all depends on one's working environment. This study investigates the attitudes, beliefs, and practices of five teaching Bekis of physical education in a public high school identified using a purposive sampling technique. The inquiry is aided by a phenomenological research approach wherein the data were gathered using an in-depth interview. The data were analyzed using thematic analysis by Lichtman's 3-Cs: coding, categorizing, and conceptualizing. The findings showed participants' challenges, life as a teaching barbie of physical education and adjustments in the real world. These findings suggest a different perspective of being gay and a teacher teaching physical education that adheres to institutional standards of authentic education. Furthermore, understanding gay physical education teachers' situation needs to be addressed to attain the so-called "chance to share in life."